Adrenal schwannoma: A case report of an unusual incidentaloma. (June 2021) - Timilsina, Sujan; Joshi, Surya Prakash; Sharma, Sujan; Kharel, Sanjeev; Karki, Shovana; Tiwari, Sansar Babu; Pandit, Durga; Parajuli, Purushottam
Abstract: Introduction and importance: Adrenal schwannomas are extremely rare tumors often misdiagnosed. The patients are usually asymptomatic while some present with non-specific abdominal pain. Only a few cases are reported to date. Case presentation: We here present a case of a 55-year-old Nepalese man presented with nonspecific abdominal pain at our Outpatient Department (OPD) found to have mass on ultrasonography of abdomen. On further investigation with Contrast Enhanced Computerized Tomography (CECT) of the abdomen and pelvis, a well-defined heterogeneous adrenal mass of size (7.8 ∗ 8.3 ∗ 6) cm with foci of calcification was seen in the left retroperitoneum. The intraoperative finding of adrenal mass and histopathology of resected mass was suggestive of schwannoma arising from the adrenal gland which was further confirmed by immunohistochemistry. Clinical discussion: Adrenal schwannoma can mimic tumors like pheochromocytoma, adrenal adenoma, cortical carcinoma, neuroblastoma, and other masses. Only 1–3% of schwannomas are retroperitoneal. Radiological findings of this tumor are non-suggestive. The histological section shows spindle cells with Antoni A and Antoni B regions while positive staining of S-100 protein in Immunohistochemistry. Conclusion: The diagnosis of adrenal schwannoma in the retroperitoneum is often challenging. The treatment of choice is surgical resection with a good prognosis. Highlights: Adrenal schwannomas are extremely rare tumors. These tumors are mostly found incidentally and often asymptomatic. Complete surgical resection of the tumor is a must for good prognosis.